Education “aspire to develop a prosperous country happiness” for students, contributing to realization the party's line in new conditions - Trương Thị Hoài; Đàm Văn Đình (Tạp chí Nghiên cứu Khoa học Công đoàn, 2024)
The "aspiration to develop a prosperous and happy country" of current students is influenced by many factors, especially the trend of globalization, the impact of the negative side of the market economy and the sabotage of foreign countries. hostile force. Therefore, educating students about the aspiration to build and develop the country is an important requirement and responsibility of the school, family, political system and the entire society. Based on clarifying the issues raised in educating students about the aspiration to develop a prosperous and happy country, the author proposes a number of solutions that contribute to improving the quality and effectiveness of education in this content for students. with students in the current period.